PELAYANAN BANK SYARIAH TERHADAP KEPUASAN NASABAH - Hikmah Dwi Astuti (Jurnal At Taajir, 2020)
The purpose of this study is to find out yourself and judge how much influence the quality of care and the profit sharing banking system on customer satisfaction, so it can be a reference for Islamic banking in the retrieval decision. This type of research is survey research on depositors in Islamic banks to take a sample from a population and used a questionnaire as a measurement of the main data collection. Subsequent to the observations and perform data analysis and hypothesis testing, it can be concluded that the results of statistical regression analysis is submitted there is significant relationship between quality of care and the profitsharing banking system on customer satisfaction